2005
DOI: 10.4049/jimmunol.174.7.3880
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular ATP Induces Cytokine Expression and Apoptosis through P2X7 Receptor in Murine Mast Cells

Abstract: Extracellular ATP and other nucleotides act through specific cell surface receptors and regulate a wide variety of cellular responses in many cell types and tissues. In this study, we demonstrate that murine mast cells express several P2Y and P2X receptor subtypes including P2X7, and describe functional responses of these cells to extracellular ATP. Stimulation of bone marrow-derived mast cells (BMMC), as well as MC/9 and P815 mast cell lines with millimolar concentrations of ATP, resulted in Ca2+ influx acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 60 publications
5
76
1
2
Order By: Relevance
“…Expression of P2X 1 receptor was confirmed by FACS while expression of P2X 3 receptor by immunoblotting [54]. Interestingly, BMMCs do not express the P2X 4 receptor on the surface, as was shown by FACS analysis and confirmed by immunoblotting, despite the presence of mRNA transcript [9,54]. This could be explained by the recent finding that P2X 4 receptor contains a non-canonical tyrosine-based sorting motif which leads to constitutive endocytosis and recycling of the P2X 4 receptor [55].…”
Section: Expression Of P2 Receptors On Mast Cellsmentioning
confidence: 81%
See 4 more Smart Citations
“…Expression of P2X 1 receptor was confirmed by FACS while expression of P2X 3 receptor by immunoblotting [54]. Interestingly, BMMCs do not express the P2X 4 receptor on the surface, as was shown by FACS analysis and confirmed by immunoblotting, despite the presence of mRNA transcript [9,54]. This could be explained by the recent finding that P2X 4 receptor contains a non-canonical tyrosine-based sorting motif which leads to constitutive endocytosis and recycling of the P2X 4 receptor [55].…”
Section: Expression Of P2 Receptors On Mast Cellsmentioning
confidence: 81%
“…We have shown that P815 mastocytoma cells (derived from DBA/2 mice) express mRNA for all P2X and P2Y receptors, while BMMCs derived from C57BL/6 mice express mRNA for P2X [1][2][3][4] , P2X [6][7] , and all P2Y receptors with the exception of P2Y 2 [9]. MC/9 cells (derived from fetal liver of a (B6 X A/J)F 1 mouse) express P2X 1-2 , P2X 4 , P2X 6-7 , P2Y 6 , P2Y 13 , and P2Y 14 receptors [9]. The expression of P2X 7 receptor protein on BMMCs, P815, and MC/9 cells was shown by immunoblotting analysis [9] and fluorescenceactivated cell sorter (FACS) [54].…”
Section: Expression Of P2 Receptors On Mast Cellsmentioning
confidence: 93%
See 3 more Smart Citations